Management of the Acute Loss of a Free Flap to the Head and Neck—A Multi‐institutional Review. (27th July 2020) - Bender‐Heine, Adam; Sweeny, Larissa; Curry, Joseph M.; Petrisor, Daniel; Young, Gavin; Hyzer, Jeffrey; Cave, Taylor; Li, Ryan; Cannady, Steven; Miles, Brett; Wax, Mark K.
Abstract : Objectives/Hypothesis: To review the management of failed free tissue transfers among four large institutions over a 13‐year period to provide data and analysis for a logical, algorithmic, experience‐based approach to the management of failed free flaps. Study Design: Retrospective case series. Methods: A multi‐institutional retrospective chart review of free tissue transfers to the head and neck region between 2006 and 2019 was performed. Patients with a failed free flap during their hospitalization after surgery to the head and neck were identified and reviewed. Patient age, co‐morbidities, risk factors, flap characteristics, tumor specifics, and length of hospital stay were reviewed, collected, and analyzed. Results: One hundred eighteen flap failures met criteria. The most common failed flap in this review was the osteocutaneous flap 52/118 (44%). The recipient site of the initial free flap ( P < .001) was the only statistically significant parameter strongly correlated with management. Osteocutaneous flap failures, fasciocutaneous, bowel, and muscle‐only flaps tended to be managed most commonly with a second free flap. Myocutaneous flap failures were managed equally with either a second free flap or a regional flap. Conclusions: The most important factor in management of a failed free flap is the recipient site. A second free flap is often the preferred treatment, but in the acute setting, local or regional flaps may be viable options depending on the recipient site, circumstances of flap loss, and patient‐ specific comorbidities. An algorithm for management of the acute flap loss is presented in this review. Level of Evidence: 4 Laryngoscope, 131:518–524, 2021